Impact of battery electric vehicles on ventilation design for road tunnels: A review. (April 2023) - Wang, Xu; Wang, Mingnian; Jiang, Ruolan; Xu, Jiani; Li, Bingtian; Wang, Xiao; Lei, Mingyu; Su, Pengfei; Liu, Chaopeng; Yang, Qianru; Yu, Jianle
Graphical abstract: Highlights: The impact of battery electric vehicles on tunnel ventilation design was reviewed. BEVs still produce non-exhaust PM, which accounts for 85% of total PM. The PM generated by BEV may be comparable to their ICEV counterparts. The average heat release rate of BEV is comparable to their ICEV counterparts. Water is still suitable for putting out battery electric vehicle fires. Abstract: Over the next several years, the proportion of battery electric vehicles (BEVs) in road tunnels is anticipated to increase as governments throughout the world promote BEVs to minimize environmental pollution. However, the research on emission factors and fire characteristics of BEVs is not as mature as that of conventional internal combustion engine vehicles (ICEV). As a result of these changes, the impact of BEVs on ventilation design for road tunnels needs to be considered in detail. This review analyzes the expected impact of BEVs on road tunnel ventilation by investigating the existing literature on emission factors and fire characteristics of BEVs. The results of current literature studies show that although exhaust emissions have been eliminated, BEVs still generate non-exhaust particles, which account for more than 85% of the total traffic particles. Due to the relatively large vehicle weight, non-exhaust particles produced by BEVs may be comparable to the total traffic particles emitted by their ICEVs counterparts. The average heat release rate of BEVs fire is similar to that of their ICEVs counterparts, but the HF concentration generated is higher, and water is still suitable for eliminating BEVs fire. At present, the impact of BEVs on tunnel ventilation design is not obvious. This review is expected to broaden the understanding of BEV emission factors and fire characteristics, which can provide some reference for road tunnel policymakers and ventilation designers.